Centromedian thalamic nucleus with or without anterior thalamic nucleus deep brain stimulation for epilepsy in children and adults: A retrospective case series. (January 2021) - Alcala-Zermeno, Juan Luis; Gregg, Nicholas M.; Wirrell, Elaine C.; Stead, Matt; Worrell, Gregory A.; Van Gompel, Jamie J.; Lundstrom, Brian Nils
Highlights: Despite advances, there are few treatments for generalized, multifocal, poorly localized, and posterior onset drug-resistant epilepsies. Centromedian with or without anterior thalamic nuclei deep brain stimulation was associated with a 63% responder rate and 58% median seizure frequency reduction. CM with or without ANT DBS was associated with reduced epilepsy severity and improved life satisfaction. There was no difference in median seizure frequency reduction and responder rate in patients with simultaneous CM + ANT DBS compared to CM DBS alone. Simultaneous CMT + ANT DBS is feasible and safe with similar adverse event rates to large prospective controlled studies of DBS for epilepsy. Abstract: The centromedian (CM) and anterior nucleus of the thalamus (ANT) are deep brain stimulation (DBS) targets for management of generalized, and focal drug resistant epilepsy (DRE), respectively. We report on a single center retrospective case series of 16 children and adults with DRE who underwent CM with simultaneous ANT (69 %) or CM without simultaneous ANT DBS (31 %). Seizure frequency, epilepsy severity, life satisfaction, and quality of sleep before and after DBS were compared. Baseline median seizure frequency was 323 seizures per month (IQR, 71–563 sz/mo). Median follow up time was 80 months (IQR 37–97 mo). Median seizure frequency reduction was 58 % (IQR 13–87 %, p = 0.002). Ten patients (63 %) reported ≥50 % seizure frequency reduction. Median seizure frequency reduction and responder rate were not significantly different for CM + ANT versus CM only. Seizure severity and life satisfaction were significantly improved. Three patients (19 %) developed device-related side effects, 2 of them (12.5 %) required surgical intervention. In a heterogenous population of children and adults with generalized, multifocal, posterior onset, and poorly localized DRE, CM with or without ANT DBS is feasible, relatively safe and is associated with reduced seizure frequency and severity, as well as improved life satisfaction.